Conservation research, policy and practice - Sutherland, William J.; Brotherton, Peter N. M.; Davies, Zoe G.; Ockendon, Nancy; Pettorelli, Nathalie; Vickery, Juliet A. (Cambridge : Cambridge University Press, 2020)
Conservation research is essential for advancing knowledge but to make an impact scientific evidence must influence conservation policies, decision making and practice. This raises a multitude of challenges. How should evidence be collated and presented to policymakers to maximise its impact? How can effective collaboration between conservation scientists and decision-makers be established? How can the resulting messages be communicated to bring about change? Emerging from a successful international symposium organised by the British Ecological Society and the Cambridge Conservation Initiative, this is the first book to practically address these questions across a wide range of conservation topics. Well-renowned experts guide readers through global case studies and their own experiences. A must-read for practitioners, researchers, graduate students and policymakers wishing to enhance the prospect of their work'making a difference'. This title is also available as Open Access on Cambridge Core.
Title from publisher's bibliographic system (viewed on 06 May 2020).
Keywords: Nature conservation; Conservation biology